Developing of in-service training program for teacher working with gifted learning disabled students - TORTOP, Hasan Said; ILGAZ, Gökhan (Journal for the education of gifted young scientists, 2023)
It is noteworthy that there is little research on the education of twice exceptional students. In fact, most of these studies are descriptive studies. The rarity of studies on twice exceptionality is due to the problems in diagnosis and the lack of knowledge and experience of teachers on this subject. There is no in-service training program for teachers on this subject. This research is a research on the problem of designing an in-service training program for teachers of students who twice exceptional students. This research is action research model because the researcher is both the practitioner and the researcher of the research and takes the role of an active solver for the solutions to the problem. Document analysis is suitable for the research technique in terms of designing the training program by searching and analysing the relevant literature. Selecting of participants process; Bursa province, which is a medium-development province in Turkey, was chosen for the research. In the study, a special special education rehabilitation center where learning disability and giftedness are seen together and the probability of being seen is very high was chosen. Fifteen special education teachers working in this institution formed the study group of the research. Two data collection tools was used in this research that are Teacher Needs Analysis Determination Form; It was created to determine the knowledge, experience and proficiency levels of teachers who are interested in the education of different students twice. In the creation of this form, first of all, a literature review was made, a draft form was created, and then the form was finalized by referring to the expert opinion. Teacher needs analysis form consists of 6 dimensions and 12 questions. Documents; Since there are not many documents related to the education of twice exceptionalty, documents suitable for teacher training for gifted education and learning difficulties were selected. Teacher In-Service Training Program Preparation Process; In the preparation of the in-service training program, the Taba Model, in which the inductive approach is used, was used. The program, designed as a result of the research, consists of 6 sessions and 11 instructional stages. In this program, there are 17 outcomes that are expected to be developed by teachers. For the realization of these outcomes, 15 instructional designs (activities) were created. The duration of the training program was determined as 10 hours, with an average of 40 minutes for each activity. The in-service training program prepared for students who twice exceptionality has the feature of improving teachers' self-regulation and exhibits a program approach to direct their own learning. Therefore, the activities progress on the worksheets and by giving instructions.